Photocatalytic removal using g-C3N4 quantum dots/Bi2Ti2O7 composites - Wang, Tao; Liu, Xiqing; Men, Qiuyue; Ma, Wei; Liu, Zhi; Liu, Yang; Ma, Changchang; Huo, Pengwei; Yan, Yongsheng (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2019)
In this work, a simple method to load of g-C3N4 quantum dots (CN QDs) onto Bi2Ti2O7 (BTO) microsphere with the amount of CN QDs (3, 7, 10 and 15%). The photocatalyst was used for the treatment of water pollutants under visible-light illumination, which proved that CNBTO composites showed improved photocatalytic activity matched up to pure BTO. Reformation of BTO with CN QDs enhanced the light assimilation capacity, and promoted the isolation of photo-induced electron-hole pairs. The trapping experiments and ESR were announced the holes (h+) and superoxide oxide (O2−) played the key role, and the relative mechanism of the photocatalytic process was proposed. Meanwhile, the effects of CN QDs content, pH and initial pollutant concentration on the removal efficiency of ciprofloxacin (CIP) were studied. Results showed that the CN QDs loaded on BTO presented higher photocatalytic efficiency, and an optimum value for the dosage of photocatalytic in pH 8.0. The g-C3N4 quantum dots modified Bi2Ti2O7 microsphere for enhancing separation efficiency of electron-hole pairs. [Display omitted] •The CN QDs have superior electron transfer ability and enriched light harvesting.•The CN QDs were coupled with Bi2Ti2O7 microsphere have exhibited enhanced photocatalytic activity.•The CN QDs extends the light absorption of Bi2Ti2O7 microsphere.